Malleable and Recyclable Poly(urea‐urethane) Thermosets bearing Hindered Urea Bonds. Issue 35 (4th July 2016) - Zhang, Yanfeng; Ying, Hanze; Hart, Kevin R.; Wu, Yuxiao; Hsu, Aaron J.; Coppola, Anthony M.; Kim, Tae Ann; Yang, Ke; Sottos, Nancy R.; White, Scott R.; Cheng, Jianjun
Abstract : Poly(urea‐urethane) thermosets containing the 1‐ tert ‐butylethylurea (TBEU) structure feature a reversible dissociation/association process of their covalent linkages under mild conditions. Unlike conventional thermosets, TBEU‐based poly(urea‐urethane) thermosets maintain their malleability after curing. Under high temperature (100 °C) and applied pressure (300 kPa), ground TBEU thermoset powder can be remolded to bulk after 20 min.